Bank efficiency, profitability and equity capital: evidence from developing countries. (24th November 2010) - Chan, Sok-Gee; Karim, Mohd Zaini Abd
This paper analysed the effects of profitability and equity capital on bank efficiency of commercial banks in the developing countries. To achieve the objectives, the stochastic frontier approach is used in the first stage of the analysis to obtain cost and profit efficiency scores. In the second stage, the efficiency scores obtained are regressed with a measure of bank's equity capital and profitability by using the Tobit regression model. The results show that equity to total assets ratio has a negative effect on efficiency indicating that either the use of debts in financing bank operations or less regulatory condition contribute to higher efficiency. The results also found that return on assets have a positive effect on profit efficiency suggesting the needs for efficient utilisation of banks assets.